2019
DOI: 10.5688/ajpe7222
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Sensitivity and Global Pharmacy Engagement in Africa

Abstract: Global engagement between schools and colleges of pharmacy in the United States and Africa is increasing. For a balanced and fruitful engagement, sensitivity towards the cultural and clinical needs of the people and professionals of the African region is critical. In this paper, we have divided the discussion into Southern, East, Central, and West Africa. General information about Africa, with unique aspects for individual subregions and countries, will be introduced. Stereotypes and misconceptions about the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Literature reveals that many African immigrants may also be better-prepared for the rigorous math and science-based curricula of the PharmD program than U.S.-born students due to a "western trend" of selecting highly skilled international students for immigration. 15,16 The combination of perceived need to obtain higher education to circumvent skills mismatches and strong baseline skills may explain why pharmacy represents a choice profession for many African immigrants, and why greater levels of academic success are achieved therein. Additionally, the field is often emphasized within their countries of origin, accompanied by more recent advocacy efforts to grow the profession within these countries.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reveals that many African immigrants may also be better-prepared for the rigorous math and science-based curricula of the PharmD program than U.S.-born students due to a "western trend" of selecting highly skilled international students for immigration. 15,16 The combination of perceived need to obtain higher education to circumvent skills mismatches and strong baseline skills may explain why pharmacy represents a choice profession for many African immigrants, and why greater levels of academic success are achieved therein. Additionally, the field is often emphasized within their countries of origin, accompanied by more recent advocacy efforts to grow the profession within these countries.…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs, evidence show that the majority of licensed pharmacists work in the community pharmacy setting. 74 , 75 , 76 A Cochrane review of the effect of pharmacist-clinical interventions in LMICs revealed that PC may improve chronic diseases clinical outcomes (blood sugar, BP and lipids levels, visits to GPs, and hospitalization rates), humanistic outcome (HRQoL). 77 Despite these potential positive impacts of pharmacists' interventions, governments of most of these countries have not officially integrated CPs into their national primary healthcare systems.…”
Section: A Snapshot Of Community Pharmacists' Involvement In Chronic ...mentioning
confidence: 99%
“…Due to the lack of legislation to support the primary care role of CPs in most LMICs, 76 , 86 there is a lack of recognition of pharmacy services and the CP is not recognized as a member of the healthcare team.…”
Section: The Key Barriers That Could Impede Chronic Disease Managemen...mentioning
confidence: 99%
“…Within pharmacy-specific collaborations, important conversations around issues such as cultural sensitivity are happening, and scholars have provided guidance specific to countries and regions of the world. 24 , 25 , 26 , 27 These must be broadened to provide a historical context and a deeper understanding on the complexities of the global health space, including issues related to power imbalances across collaborating partners. Recent calls to decolonize global health 28 speak to these power imbalances and are important reminders for working towards a more equitable and just global health partnership in program design, implementation, knowledge production, and many related issues.…”
Section: Introductionmentioning
confidence: 99%